Mental health in Austrian psychotherapists during the COVID-19 pandemic - Schaffler, Yvonne; Kaltschik, Stefan; Probst, Thomas; Jesser, Andrea; Pieh, Christoph; Humer, Elke (Frontiers in Public Health, 2022)
Although the impact of the COVID-19 pandemic on mental health has been reported in different communities, little is known about the mental health of psychotherapists during the COVID-19 pandemic. This study aimed to assess mental health during the COVID-19 pandemic in Austrian psychotherapists and compare it with the general population. A total of n = 513 psychotherapists (80.5% women; mean age: 53.06 ± 9.94 years) took part in an online survey conducted from April to June 2022. At the same time, a representative sample (N = 1,031) of the Austrian general population was surveyed online. Indicators of mental health were mental wellbeing (WHO-5), depression (PHQ-2), anxiety (GAD-2), insomnia (ISI-2), and stress (PSS-10). The general population sample was matched according to age and gender with the psychotherapist's data using propensity scores, yielding a final sample of n = 513 (80.5% women; mean age: 52.33 ± 13.39 years). Psychotherapists showed lower odds for exceeding cut-offs for clinically relevant depressive, anxiety, insomnia and stress symptoms (0.34–0.58) compared to the general population. Further studies should elucidate the protective factors underlying these findings.